2004
DOI: 10.1158/1078-0432.ccr-03-0537
|View full text |Cite
|
Sign up to set email alerts
|

CD95-Mediated Apoptosis Is Impaired at Receptor Level by Cellular FLICE-Inhibitory Protein (Long Form) in Wild-Type p53 Human Ovarian Carcinoma

Abstract: Purpose: Ovarian carcinoma is a highly lethal malignancy that often becomes resistant to chemotherapy. Alterations in apoptotic signals and p53 status contribute to drug resistance, and CD95-mediated apoptosis is also deficient in resistant cells. We analyzed the mechanism of resistance to CD95-mediated apoptosis in ovarian carcinoma cell lines differing in p53 status.Experimental Design: CD95-mediated apoptosis was induced by agonistic anti-CD95 antibody, and the apoptotic cascade was monitored with biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 35 publications
4
40
0
Order By: Relevance
“…In addition, c-FLIP L expression was higher in p53 wild-type tumors than in p53-mutated tumors (Table 3). A similar result was also reported for ovarian carcinoma, indicating that c-FLIP L overexpression was more common in p53 wild-type tumors than in p53-mutated tumors (31). The positive correlation between FasL and c-FLIP L in lung tumors and their prognostic significance were also observed in colorectal and bladder urothelial carcinomas (23,43).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, c-FLIP L expression was higher in p53 wild-type tumors than in p53-mutated tumors (Table 3). A similar result was also reported for ovarian carcinoma, indicating that c-FLIP L overexpression was more common in p53 wild-type tumors than in p53-mutated tumors (31). The positive correlation between FasL and c-FLIP L in lung tumors and their prognostic significance were also observed in colorectal and bladder urothelial carcinomas (23,43).…”
Section: Discussionsupporting
confidence: 79%
“…Anti-FasL (1/500) polyclonal primary antibody (N-20; Santa Cruz Biotechnology) and anti-c-FLIP L (1/100) polyclonal primary antibody (C-19; Santa Cruz Biotechnology) were used (26,31). An immunohistochemistry detection kit for in vitro diagnostic use (Invitrogen) was used according to the standard protocol.…”
Section: Translational Relevancementioning
confidence: 99%
“…An association between c-FLIP expression and resistance to apoptosis mediated by CD95 as well as by TRAIL has been reported for several cancer types (Abedini et al 2004, Rippo et al 2004, Horak et al 2005, Longley et al 2006, Rogers et al 2007, and c-FLIP expression was already reported to be an unfavorable prognostic indicator in some oncotypes other than ovarian carcinoma (Chen et al 2005, Valnet-Rabier et al 2005, Ullenhag et al 2007). In EOC cell lines, we have recently identified the long isoform of c-FLIP (c-FLIP L ) as one of the molecules directly involved in the impairment of apoptotic signaling in the context of functional p53; in the same study, we also found an inverse relationship between c-FLIP L overexpression and p53 nuclear accumulation in a small number of EOC specimens (Mezzanzanica et al 2004). Additionally, Tsang's group reported the involvement of c-FLIP L in regulating EOC cisplatin sensitivity in concert with p53 and the ubiquitin ligase Itch (Abedini et al 2004(Abedini et al , 2008, further suggesting a role for c-FLIP L as a survival factor in EOC cell lines.…”
Section: Introductionmentioning
confidence: 54%
“…15 Briefly, tissue lysates were obtained from ovarian tumor specimens collected as cryostatic sections (10/ specimen, 5 lm each), directly solubilized with loading buffer and boiled for 5 min at 95°C. Lysates (40 lg in the case of cell lines and half of the sample in the case of tumor specimens) were separated by 10% SDS-PAGE and transferred to a nitrocellulose membrane (Hybond C-Super, Amersham).…”
Section: Western Blotting Analysis Of M-cam Expressionmentioning
confidence: 99%